Exploring Blacks' Perceptions of Whites' Racial Prejudice as a Function of Intergroup Behavior and Motivational Mindsets. Issue 5 (July 2019) - Simon, Stefanie; Shaffer, Emily; Neel, Rebecca; Shapiro, Jenessa
When Whites believe prejudice cannot change, they often adopt a behavioral style that is intended to reduce the possibility that they are seen as racist (i.e., performance-oriented behaviors). The present research tests the possibility that these performance-oriented behaviors may be interpreted, ironically, as racist. Across two studies, Black participants viewed performance-oriented behaviors as indicating racial prejudice. Additionally, when Black participants were led to believe that Whites' racial prejudice could not change, they perceived Whites as more prejudiced. This research highlights a potential source of misunderstanding in interracial interactions and offers implications for improving interracial interactions from target and perpetrator perspectives.